The Search for North Sea oil - Occidental North Sea Group ([London] : Occidental North Sea Group, 1976)
This booklet tells the story of how one consortium has undertaken the task of bringing oil ashore, despite the frequently daunting conditions
Cover title.
osc 13/11/2019
Loans
Keywords: Petroleum in submerged lands; Offshore oil well drilling